Effect of Fermentation on the Phsyco and Functional Properties of Red Sorghum Flour (Sorghum bicolor L.) - Lembong, Elazmanawati; Wulandari, Endah; Harlina, Putri Widyanti; Tsalitsu, Syifa (Chimica et Natura Acta, 2025)
Modification of red sorghum flour by fermentation method can improve the physical, chemical, and functional properties of the resulting sorghum flour. The purpose of this study was to determine the fermentation time that can affect the physical and functional characteristics of red sorghum flour fermented spontaneous (TSS) and non-spontaneous (TTS). Results indicated that the best treatment was red sorghum flour fermented at 24 hours both spontaneous and non-spontaneous. TSS at 24 hours had a water absorption capacity of 1.04%, oil binding capacity of 1.04%, swelling volume of 7.47%, solubility of 7.57%, initial gelatinization temperature of 76.56oC, peak viscosity of 2855 cP, hot paste viscosity of 2214 cP, breakdown viscosity of 641 cP, cold paste viscosity of 3425 cP, and setback viscosity of 1211 cP. TTS at 24 hours had a water absorption capacity of 1.21%, oil binding capacity of 1.18%, swelling volume of 7.49%, solubility of 8.23%, initial gelatinization temperature of 75.81oC, peak viscosity of 3172 cP, hot paste viscosity of 2600 cP, breakdown viscosity of 572 cP, cold paste viscosity of 5107 cP, and setback viscosity of 2507 cP.